Factors influencing level of participation of community forest associations in management forests in Kenya. (2nd April 2016) - Musyoki, Josephine Kamene; Mugwe, Jayne; Mutundu, Kennedy; Muchiri, Mbae
ABSTRACT: In Kenya, a Participatory Forest Management (PFM) approach was adopted through formation of Community Forest Associations (CFA) to improve forest cover and their livelihoods as provided for in the Forest Act 2005. The main objective of this study was to determine the factors influencing the level of CFA members' participation in PFM activities in selected forests in Kenya. The study was undertaken on the Ontukigo and Ngare Ndare CFAs involved in participatory management of the Ontulili and Ngare Ndare forests respectively, located in the Eastern Conservancy, Buuri Sub County (Meru County) in Kenya. Semi structured questionnaires were administered to randomly selected 80 CFA and 80 Non CFA members. Participatory Rural Appraisal tools, including focused group discussions and community wealth characterization, were used to collect qualitative data for precise description of the quantitative data. The level of participation of CFA members in PFM activities was positively and significantly influenced by the level of perceived PFM benefits (χ 2 = 38.73, P=0.05); range of farm size (χ 2 =12.72, P=0.05); and nature of the head-of-household (χ 2 =29.99, P=0.001). As such, benefits gained from the forest play an important role as incentives to community participation in PFM.